Kajian Psikologi Tentang â€œBelajarâ€ Dalam Al-Qurâ€™an/Hadis - Imam Hanafi (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2017)
Learning is a process taken by a person in order to get the knowledge. Science itself in Islam has a very urgent position because it will be able to deliver people to the perfection of life in the world, especially in the hereafter. In the Qur'an there are many verses that show about learning, learning principles, etc. Therefore, the "study" contained in the Qur'an or Hadith will be examined using the discipline of psychology, which by doing this study the author will provide new insights on the concept of learning produced by western scientists actually already implied clearly in the verses Verses of the Qur'an or in the hadith.